Specificity of the DNA Product of the C-Type Virus RNA-Dependent DNA Polymerase - Hatanaka, Masakazu (1971)
The specificity of the DNA product of the RNA-dependent DNA polymerase found in C-type virions was analyzed by reciprocal hybridization with RNA from viruses of mouse, hamster, cat, and viper. These tests revealed a clear species specificity for the DNA product with no detectable interspecies hybridization.